Microstrip Antenna Development for Radar Sensor - Lajos Nagy (Sensors, 2023)
Tank level measurement is an important research area in radar technology. Level measurement using radar technology is a safe solution even under extreme process conditions, such as high pressure, temperature, and vapors. Special antennas are required to meet electromagnetic requirements such as high gain, low sidelobe level, and high bandwidth. Another requirement is a small size and good manufacturability of the antenna. One promising solution is the use of microstrip antennas for tank-level measurements. This paper presents a special microstrip antenna, that meets the main requirements in addition to a circular antenna layout, which fills optimally the tank hatch. To do this, we created a special antenna layout with a suitable feeding network and added an optimized ring around the antenna system, which significantly reduces the sidelobe level. The center frequency of the antenna is 25 GHz with a 1 GHz bandwidth.